Gamification-Based “Maplalian Curik-Curik” Video on Food Chain Material for Fifth Grade Elementary School Students - Ni Made Natalia Dewi; Anak Agung Gede Agung; Didith Pramunditya Ambara (Jurnal Media dan Teknologi Pendidikan, 2026)
The low learning outcomes in science (IPAS) are influenced by the limited use of innovative learning media and the minimal integration of traditional games, resulting in low student engagement and suboptimal understanding of food chain concepts. This study aims to develop and evaluate the feasibility and effectiveness of a gamification-based instructional video, Maplalian Curik-curik, which adapts a traditional game as a contextual learning medium. This research employs a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects include content experts, instructional design experts, media experts, and elementary school students involved in individual, small group, and field trials. Data were collected through observations, interviews, questionnaires, and learning outcome tests. Data analysis techniques include qualitative and quantitative descriptive analysis, as well as inferential analysis using a t-test. The results indicate that the developed media is of very high quality in terms of content, design, and media aspects, and is proven to be effective in significantly improving students’ learning outcomes. Therefore, the gamification-based instructional video is feasible as an innovative and meaningful learning medium for science education. The findings imply the importance of integrating local cultural elements with technology in developing instructional media to enhance the quality of learning.